2010
DOI: 10.3109/07420528.2010.498067
|View full text |Cite
|
Sign up to set email alerts
|

Working the Night Shift Causes Increased Vascular Stress and Delayed Recovery in Young Women

Abstract: Shiftwork has been associated with elevated blood pressure (BP) and decreased heart-rate variability (HRV), factors that may increase the long-term risk of cardiovascular-related mortality and morbidity. This study explored the effect of shiftwork on dynamic changes in autonomic control of HRV (cardiac stress), systolic BP and diastolic BP, i.e., SBP and DBP (vascular stress), and recovery in the same subjects working different shifts. By studying the same subjects, the authors could reduce the effect of possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 41 publications
(38 reference statements)
3
43
0
3
Order By: Relevance
“…Gece vardiyası çalışması anlamlı stresle ilişkilidir ve endojen nokturnal kan basıncı düşüşünü engeller. Nokturnal kan basıncı yükselir ve bu durum ertesi güne kadar devam eder (77). Seksen binden fazla kadın hemşirenin yer aldığı bir kohort çalışması, gece vardiyasında çalışmanın, vasküler risk faktörlerini kontrol ettikten sonra, her beş yılda %4 oranında artmış iskemik inme riski ile ilişkili olduğunu bildirmiştir (78).…”
Section: Sirkadiyen Ritim Bozuklukları Ve İnmeunclassified
“…Gece vardiyası çalışması anlamlı stresle ilişkilidir ve endojen nokturnal kan basıncı düşüşünü engeller. Nokturnal kan basıncı yükselir ve bu durum ertesi güne kadar devam eder (77). Seksen binden fazla kadın hemşirenin yer aldığı bir kohort çalışması, gece vardiyasında çalışmanın, vasküler risk faktörlerini kontrol ettikten sonra, her beş yılda %4 oranında artmış iskemik inme riski ile ilişkili olduğunu bildirmiştir (78).…”
Section: Sirkadiyen Ritim Bozuklukları Ve İnmeunclassified
“…Усло-вия труда на предприятиях нефтегазодобывающего ком-плекса связаны с непрерывным производством, то есть с ночными сменами. В ряде работ при СМАД установ-лены более высокие показатели АД, особенно систоли-ческого, во время работы в ночные смены в сравнении с дневными [16]. Работа в ночную смену является столь значимым фактором риска развития АГ, что превосходит такие факторы как возраст и ожирение [17].…”
Section: клиника и фармакотерапияunclassified
“…The data suggest an average 50% excess risk for CAD among employees with work stress. Lo et al, from Taiwan reported that shift-work may be associated with elevated blood pressure (BP) and decreased heart rate variability (HRV) [16]. This study explored the effect of shift-work on dynamic changes in autonomic control of HRV (cardiac stress), systolic blood pressure and diastolic blood pressure, (vascular stress), and recovery in the same subjects working different shifts.…”
Section: Sleep Disorders and Risk Of Noncommuni-cable Diseasesmentioning
confidence: 99%
“…These rhythms appear to have independent influence on the function of the endocrine system, circadian brain function and gastrointestinal tract [2-6, 8, 9, 11-15]. Insufficient sleep and its poor quality due to shift work interfere with beta cells functioning resulting in to risk factors for the development and exacerbation of insulin resistance [9][10][11][12][13]16]. Sleep disorders may cause increases in appetite, polyphasia leading to adiposity [8,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation